If it's not what You are looking for type in the equation solver your own equation and let us solve it.
30=-3y+6(y+3)
We move all terms to the left:
30-(-3y+6(y+3))=0
We calculate terms in parentheses: -(-3y+6(y+3)), so:We get rid of parentheses
-3y+6(y+3)
We multiply parentheses
-3y+6y+18
We add all the numbers together, and all the variables
3y+18
Back to the equation:
-(3y+18)
-3y-18+30=0
We add all the numbers together, and all the variables
-3y+12=0
We move all terms containing y to the left, all other terms to the right
-3y=-12
y=-12/-3
y=+4
| 7p2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 3(-2+6p)=3p-6 | | 3(-2+6p)=3p-6 | | 3(-2+6p)=3p-6 | | (8x)^2=8x^2 | | 7x−8=5x−16 | | 25=45-x | | 9(2m-)=18m-81 | | 7-2y/2-2/5(2-y)=1/1/4 | | 4u-8+2(2u+4)=-6(u+3) | | `8+4x=-10+x | | 4u-8+2(2u+4)=-6(u+3) | | -6+2v=2 | | 4(u+4)=-6u-24 | | 8x(X-2)=96 | | t+58=75 | | Y+6=3(x+1) | | Y+6=3(x+1) | | 3/2x+4=37 | | -(18+4x)=26 | | 3z/7-9=5 | | x*x=250 | | 2x+30=1.50x+12=3 | | (x*2)*(x/5)=250 | | -12=-3yy= | | -12=-3yy= | | (18-3x)-(4+2)=10 | | x/4-4+11=15 |